Response to Immune Checkpoint Inhibitor Treatment in Advanced Cervical Cancer and Biomarker Study - Shieh, Kevin R.; Huang, Anna; Xu, Yiqing (Frontiers in Medicine, 2021)
Background: Checkpoint inhibitor immunotherapy or immuno-oncology (IO) treatment in refractory cervical cancer yielded an objective response rate (ORR) of 12% in tumors expressing the programmed cell death ligand-1 (PD-L1) in the KEYNOTE-158 phase II study. We hypothesized that the positive response might be associated with the level of PD-L1 expression and/or the tumor mutation burden (TMB). We also aimed to analyze if responses could be associated with platinum sensitivity. Methods: This is a retrospective study of all consecutive patients with cervical cancer who received pembrolizumab or nivolumab. Results: Ten patients were identified. Median age was 64.5 years old (range 48–80). The response rate was 70% and the median duration of response was 21.0 months (range 1.8–26.7) after 20.7 months of follow-up (range 2.0–31.0). The response rate was 80% in patients with PD-L1 combined positive score (CPS) ≥ 10, and 75% in patients with tumor mutation burden (TMB) ≥ 10 mut/Mb. The mean progression-free survival (PFS) for the entire cohort was 20.2 months (95% CI 12.0–28.5). Seven patients had treatment for >12 months (range 14.6–31.0). Five patients were platinum-sensitive and 5 patients were platinum-resistant at the time of immunotherapy, and the response rate was similar regardless of platinum sensitivity. Conclusions: The positive response to IO treatment in advanced cervical cancer in this study was higher than published, and a possible association with the level of PD-L1 expression and the TMB level was suggested. A PD-L1 CPS score ≥ 10 or TMB ≥ 10 may be biomarkers to correlate with response, which should be explored in large studies.